2022
DOI: 10.1038/s41598-022-08927-1
|View full text |Cite
|
Sign up to set email alerts
|

Alginate oligosaccharides enhance diffusion and activity of colistin in a mucin-rich environment

Abstract: In a number of chronic respiratory diseases e.g. cystic fibrosis (CF) and chronic obstructive pulmonary disease (COPD), the production of viscous mucin reduces pulmonary function and represents an effective barrier to diffusion of inhaled therapies e.g. antibiotics. Here, a 2-compartment Transwell model was developed to study impaired diffusion of the antibiotic colistin across an artificial sputum (AS) matrix/medium and to quantify its antimicrobial activity against Pseudomonas aeruginosa NH57388A biofilms (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Three highly biofilm-forming isolates were selected, which were named S.t1, S.t.3, and S.t.2 and the statistical analysis showed significant differences. Clear with a significant level of significance (P > 0.05) between the inhibitory effects of the studied components of both types of lactobacilli on the isolates of S. Typhi as in Figure (1)(2)(3)(4)(5). respectively, while the lowest inhibition zone was with a diameter of 15 mm for the two isolates S.t.2 and S.t.3 caused by the effect of suspended bacteria L.plantarum as in Table (1)(2)(3)(4)(5), and as a result of the results shown, the L. plantarum CFS was approved in subsequent experiments to inhibit and kill S. Typhi and prevent it from forming a biofilm.…”
Section: Figure (1-3): the Congo Red Methodsmentioning
confidence: 95%
See 3 more Smart Citations
“…Three highly biofilm-forming isolates were selected, which were named S.t1, S.t.3, and S.t.2 and the statistical analysis showed significant differences. Clear with a significant level of significance (P > 0.05) between the inhibitory effects of the studied components of both types of lactobacilli on the isolates of S. Typhi as in Figure (1)(2)(3)(4)(5). respectively, while the lowest inhibition zone was with a diameter of 15 mm for the two isolates S.t.2 and S.t.3 caused by the effect of suspended bacteria L.plantarum as in Table (1)(2)(3)(4)(5), and as a result of the results shown, the L. plantarum CFS was approved in subsequent experiments to inhibit and kill S. Typhi and prevent it from forming a biofilm.…”
Section: Figure (1-3): the Congo Red Methodsmentioning
confidence: 95%
“…Clear with a significant level of significance (P > 0.05) between the inhibitory effects of the studied components of both types of lactobacilli on the isolates of S. Typhi as in Figure (1)(2)(3)(4)(5). respectively, while the lowest inhibition zone was with a diameter of 15 mm for the two isolates S.t.2 and S.t.3 caused by the effect of suspended bacteria L.plantarum as in Table (1)(2)(3)(4)(5), and as a result of the results shown, the L. plantarum CFS was approved in subsequent experiments to inhibit and kill S. Typhi and prevent it from forming a biofilm. The results showed that L. plantarum has a clear inhibitory effect towards S.Typhi, but there is a discrepancy in this effect according to the type of isolate, as the diameters of the highest inhibition were for the CFS, which includes many inhibitory and lethal substances for pathogens, due to its production of secondary metabolic products such as microbial antibiotics,such as bacteriocins (11).…”
Section: Figure (1-3): the Congo Red Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…It remains to be shown whether the recent pharmacological restoration of functionality of the cystic fibrosis transmembrane conductance regulator CFTR, that leads to diminished growth of pathogens and re-establishment of a conventional microflora, can be mimicked by altering the composition of the artificial sputum medium. Artificial medium use reflecting distinctly similar host conditions can also be applied to specifically monitor bacterial colonization in primary ciliary dyskinesia and chronic obstructive pulmonary diseases (COPD) [ 73 , 74 ].…”
Section: Assessment Of Antimicrobial Tolerance Mimicking the Host Milieumentioning
confidence: 99%